Management of glaucoma with neuroprotective drug - Islam, Md Nurul (Bangladesh Journal of Medical Science, 2010)
Glaucoma is an optic neuropathy characterized by progressive loss of retinal ganglion cells (RGCs). Death of ganglion cells is not always only pressure dependent mechanism but also have several pressure independent mechanism that establish a cascade of changes that ultimately leads to cell death. Neuro- protection is a process that attempt to preserve the cells that were spared during initial insult, but are still vulnerable to damage. Although not yet available, a neuroprotective agent would be great use that rescue neurons already compromised or that promote regrowth of axonal or dendritic connection to restore function. This review based on literature, giving the idea of varies mechanism of RGC death delineated by research and discussed some pharmacological agent believed to have a neuroprotective role in glaucoma. DOI: 10.3329/bjms.v9i4.6685 Bangladesh Journal of Medical Science Vol.09 No.4 July 2010 pp.199-203